How much income and wealth inequality: The rise of income and wealth inequality in america: Evidence from distributional macroeconomic accounts - Saez, Emmanuel and Zucman, Gabriel (The Journal of Economic Perspectives)
This paper studies inequality in America through the lens of distributional macroeconomic accounts$1 (Bcomprehensive distributions of the aggregate amount of income and wealth recorded in the official macroeconomic accounts of the United States. We use these distributional macroeconomic accounts to quantify the rise of income and wealth concentration since the late 1970s, the change in tax progressivity, and the direct redistributive effects of government intervention in the economy. Between 1978 and 2018, the share of pre-tax income earned by the top 1 percent rose from 10 percent to about 19 percent, and the share of wealth owned by the top 0.1 percent rose from 7 percent to about 18 percent. In 2018, the tax system was regressive at the top-end; the top 400 wealthiest Americans paid a lower average tax rate than the macroeconomic tax rate of 29 percent. We confront our methods and findings with those of other studies, pinpoint the areas where more research is needed, and describe how additional data collection could improve inequality measurement.s
Keywords: Income, Wealth inequality, Wealth inequality - America, Distributional macroeconomic accounts